The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s40064-015-1561-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic description of a tick-borne encephalitis virus strain Sofjin with the longest history as a vaccine strain

Abstract: Vaccines based on the strain Sofjin of the Far-Eastern tick-borne encephalitis virus (TBEV) subtype have been used for TBE prophylaxis for over 50 years in Russia and neighboring countries. On the wide territory, where all known TBEV subtypes are circulating, the cultural, purified, concentrated, inactivated TBE vaccine Moscow has been shown to be safe and efficacious in a massive immunization. In the present work, we describe the genome of the vaccine strain Sofjin. We have shown that it differs from TBEV str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 6 publications
(11 reference statements)
1
20
0
2
Order By: Relevance
“…TBEV strains (Table 1 ) were described previously (Gritsun et al, 1997 ; Romanova et al, 2007 ; Zlobin et al, 2007 ; Kozlovskaya et al, 2010 ; Vorovitch et al, 2015 ; Chernokhaeva et al, 2016b ; Shevtsova et al, 2016 ). The viruses were stored at −70°C as a 10% mouse brain suspension or a culture supernate (CS) of infected PEK cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TBEV strains (Table 1 ) were described previously (Gritsun et al, 1997 ; Romanova et al, 2007 ; Zlobin et al, 2007 ; Kozlovskaya et al, 2010 ; Vorovitch et al, 2015 ; Chernokhaeva et al, 2016b ; Shevtsova et al, 2016 ). The viruses were stored at −70°C as a 10% mouse brain suspension or a culture supernate (CS) of infected PEK cells.…”
Section: Methodsmentioning
confidence: 99%
“…Preventive vaccination is a primary prophylactic tool against TBE. Inactivated, purified, concentrated vaccines for adults and children based on FE strains Sofjin (Elbert et al, 1980 ; Vorovitch et al, 2015 ), 205 (Safronov et al, 1991 ; Karpova et al, 1995 ), and Senzhang (Zhang et al, 2012 ; Xing et al, 2017 ) and on Eur strains Neudoerfl (Ecker et al, 1999 ; Loew-Baselli et al, 2011 ) and K23 (Ecker et al, 1999 ; Zent et al, 2003 ) are available. Clinical trials have demonstrated their immunogenicity (Vorob'eva et al, 1983 ; Pavlova et al, 1999 ; Amicizia et al, 2013 ; Vorovitch et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Для вакцинации использовали вакцину «Клещ-Э-Вак» (доза 0,5 мл, серия № 3.2009ж), представ-ляющую собой очищенную концентрированную суспензию инактивированного формалином вируса КЭ, сорбированного на алюминии гидроксиде. Действующим началом вакцины является специфический антиген штамма Софьин вируса КЭ (GenВank KC806252) [9]. Содержание белка Е в дозе вакцины составляет 0,90±0,15 мкг.…”
Section: материал и методыunclassified
“…In the last two decades, considerable attention has been paid to TBE vaccine reactogenicity owing to a significantly increased number of vaccinated individuals, as well as a changing group composition and an expansion of the groups being vaccinated against TBE (e.g., children older than 1 year and elderly individuals) [6,7]. e most widely used TBE vaccine in Russia is licensed for people 3 years old and older and is the universal lyophilized "TBE vaccine Moscow" vaccine, which is based on the Sofjin strain of the FE subtype [1,8].…”
Section: Introductionmentioning
confidence: 99%